2021
DOI: 10.17660/ejhs.2021/86.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Germination and seedlings response of bermudagrasses under water submersion

Abstract: De Luca et al., 2008) including species choice. Due to climate changes, warm-season species, and especially bermudagrass, are becoming popular in the transition zones of Europe (Macolino et al., 2016). However, only a few studies have investigated the effect of increased rainfall intensity on early-stage growth of warm-season turf species. Heavy or total plant submersion, or waterlogging when plants are not submerged but soil pores are saturated (Bailey-Serres et al., 2012; Striker, 2012). Waterlogging and, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The high seedling tolerance to waterlogging found in this experiment is in line with the findings of Giolo et al. (2021), who observed, in a greenhouse experiment, signs of suffering only after 6 days of complete submersion. Differences among cultivars for percentage GC observed agree with previous studies that reported differences in the speed of establishment among bermudagrass cultivars (Giolo et al., 2020; Magni et al., 2014; Patton et al., 2008).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The high seedling tolerance to waterlogging found in this experiment is in line with the findings of Giolo et al. (2021), who observed, in a greenhouse experiment, signs of suffering only after 6 days of complete submersion. Differences among cultivars for percentage GC observed agree with previous studies that reported differences in the speed of establishment among bermudagrass cultivars (Giolo et al., 2020; Magni et al., 2014; Patton et al., 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Giolo et al. (2021) compared five cultivars of bermudagrass (Jackpot, La Paloma, Transcontinental, Yukon, and Sunbird) in the laboratory and the greenhouse and observed that seeds and seedlings were tolerant to floating or submerged conditions for up to 6–8 days. In another greenhouse study, Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation